REVIEW OF CHANGES IN BUILDING TYPOLOGY IN COLONIAL AREAS: CASE STUDY OF CIPAGANTI HOUSING AREA - Tahira Chandra (Kohesi: Jurnal Sains dan Teknologi, 2025)
Cipaganti is one of the areas that experienced growth. This research examines changes in building typology in the area using a qualitative approach. The buildings in this area have changed over time. Changes such as the shape of the building, and the function of the building occur a lot in this area, because of the rapid development of the period that makes the Cipaganti area one of the commercial areas, some buildings switch functions. Policies that support the preservation of historic buildings, education to the public about the importance of historical value, and strict supervision of new developments are steps that need to be taken to ensure that Cipaganti can remain an area that has historical value.